Pow-Tech Egg Enterprise / Noorfadlyana Mail ... [et al.] - Mail, Noorfadlyana; Azuddin, Siti Nur Amirah; Kadis, Siti Fadhilah; Mashuri, Nurilyani; Sabli, Norain (Faculty of Applied Sciences, 2006)
POW-TECH-EGG is involved in the manufacturing, production and distribution of "powdered, liquid and frozen egg". The business has identified its target market in Selangor. The factory is located at Pt 6166, Jalan Enggang, Kampung Kebun Baru, Batu 9 42500, Telok Panglima Garang, Kuala Langat , Selangor. POW-TECH-EGG major market segments within the target area are all consumer in Selangor such as housewife, chef hotel and restaurant and so on. Looking at industry overview there was a competitor that offer similar product to the same target market. However, they are not considered competitors because they do not produce "powdered, liquid and frozen egg". The competitions are from Egg Company in Selangor.